Cd-MOF material based on aromatic tetracarboxylic acid ligand and preparation method and application thereof

CN122978463APending Publication Date: 2026-10-27XI'AN PETROLEUM UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611260867.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

针对不同类型目标离子分别获得明显且可区分的荧光响应,需要材料的结构和荧光性质能够同时适应不同检测体系,因此材料设计和性能调控更加困难

Benefits of technology

一种基于芳香四羧酸配体的Cd-MOF材料,以Cd2+作为金属中心,以4,4′,4″,4-([6,6′-联苯并吡嗪]-2,2′,3,3′-四基)四苯甲酸的三负离子HL³-作为配位连接体,使Cd2+与HL3-配位形成金属有机框架,所得Cd-MOF材料还包括Me2NH2+离子、DMA分子和晶格水分子;该芳香四羧酸配体具有较大的共轭体系,为材料的荧光发射提供结构基础;所得Cd-MOF具有明确的晶体结构,并能够对Fe3+和Cr2O72-产生明显的荧光猝灭响应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978463A_ABST
    Figure CN122978463A_ABST
Patent Text Reader

Abstract

The application discloses a Cd-MOF material based on aromatic tetracarboxylic acid ligand and a preparation method and application thereof, and belongs to the technical field of fluorescent recognition and detection materials. 2+ The Cd-MOF material takes Cd 2+ as a metal center, takes trianion H4L 3‑ as a coordination linker, and forms a metal organic framework by coordination of Cd 3‑ and H4L + . The Cd-MOF material further comprises Me2NH2 2+ ion, N,N-dimethylacetamide molecule and lattice water molecule. The aromatic tetracarboxylic acid ligand H4L and cadmium salt are placed in a mixed system of N,N-dimethylacetamide, H2O and HNO3, and are subjected to ultrasonic mixing and solvothermal reaction to obtain the Cd-MOF material. The Cd-MOF material can recognize Fe 3+ and Cr2O7 2‑ by fluorescence quenching, and has good selectivity, anti-interference ability and detection sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fluorescent recognition and detection materials technology, specifically relating to a Cd-MOF material based on aromatic tetracarboxylic acid ligands, its preparation method, and its application. Background Technology

[0002] With the rapid development of human society and industry, large amounts of pollutants such as harmful ions and organic matter are released into the environment, which can adversely affect human health and the living environment of other organisms. Therefore, the rapid and accurate detection of pollutants in the environment and the corresponding emission control have become important research topics in related fields. Among these, the detection of ions such as iron ions and dichromate ions has a high practical demand.

[0003] Currently, ion detection methods mainly include spectrometry, chromatography, and chemical titration. Spectrometry includes atomic absorption spectrophotometry, inductively coupled plasma mass spectrometry, and fluorescence spectroscopy, while chromatography includes ion chromatography and high-performance liquid chromatography. Different detection methods have their own characteristics in terms of detection sensitivity, instrument requirements, operation procedures, and detection costs. Among them, fluorescence spectroscopy has attracted widespread attention due to its advantages such as fast detection speed, high sensitivity, good selectivity, strong anti-interference ability, reusability, and relatively low cost.

[0004] One of the key aspects of fluorescence spectroscopy detection is obtaining recognition materials capable of producing a significant fluorescence response to target ions. For complex ionic systems, the sample often contains multiple cations or anions, and different ions may produce similar fluorescence enhancement, fluorescence quenching, or other spectral changes in the fluorescent material. Therefore, simply increasing the fluorescence emission intensity of the material itself does not directly guarantee good recognition ability for the target ion; the fluorescence response produced by the target ion must also be significantly different from the responses of other coexisting ions. This presents a challenge in balancing luminescence performance, selectivity, and anti-interference capabilities in fluorescent recognition materials.

[0005] Metal-organic frameworks (MOFs) are a class of crystalline materials formed by coordination bonds between metal ions or metal clusters and organic ligands. They possess characteristics such as designable structures, porosity, and high specific surface area. To obtain MOF materials with fluorescent properties, current research typically selects organic ligands containing large conjugated systems and combines them with Eu... 3+ 、Tb 3+ Zn 2+ and Cd 2+ Metal ions coordinate and assemble. Among them, Cd-MOF has certain fluorescence properties, and there are already related studies on its application in ion fluorescence recognition.

[0006] However, the fluorescence and ion recognition properties of Cd-MOF materials are not only related to the metal center, but also influenced by various factors such as the structure of the organic ligands, the coordination mode, and the final framework structure. Different ligands and Cd... 2+ The resulting coordination structures differ, and even if the material itself exhibits strong fluorescence, it may not necessarily produce a discriminative fluorescence response to a specific analyte ion. Therefore, when designing Cd-MOF fluorescent recognition materials, existing techniques cannot simultaneously achieve strong fluorescence emission performance and high ion recognition selectivity simply by replacing the metal ion or organic ligand.

[0007] Furthermore, simultaneously recognizing different types of ions is even more challenging. Iron ions (Fe) 3+ It belongs to the category of metal cations, while dichromate ions (Cr₂O₇) are... 2- As an anion, Cd-MOFs exhibit significantly different chemical properties and interactions with fluorescent materials. While some Cd-MOFs with fluorescent recognition capabilities have been reported, achieving the same level of fluorescence recognition as Fe is still a challenge. 3+ and Cr2O7 2- Materials capable of selective recognition are relatively few. To obtain distinct and differentiated fluorescence responses for different types of target ions, the material's structure and fluorescence properties must be adaptable to different detection systems, making material design and performance tuning more challenging.

[0008] Furthermore, for practical ion detection, the material also needs to have good anti-interference capabilities. In Fe... 3+ Na may be present in the detection system. + K + Mg 2+ Al 3+ Ca 2+ Zn 2+ And other cations; in Cr2O7 2- F may also exist in the detection system. - Cl - ,Br - NO3 - H2PO4 - SO4 2- CO3 2- Anions are also present. How to ensure that the fluorescence changes caused by the target ion maintain sufficient distinguishability in the presence of multiple coexisting ions, while simultaneously maintaining response sensitivity at lower detection concentrations, is a challenge that needs to be addressed for the further application of existing fluorescent recognition materials.

[0009] Therefore, existing Cd-MOF fluorescent recognition materials still need to achieve a balance between fluorescence emission performance, target ion selectivity, anti-interference ability of coexisting ions, and detection sensitivity, especially how to obtain materials suitable for Fe3+ and Cr2O7 2- Cd-MOF fluorescent recognition materials for detecting different types of ions still require further research and improvement. Summary of the Invention

[0010] The technical problem to be solved by this invention is to address the shortcomings of the prior art by providing a Cd-MOF material based on aromatic tetracarboxylic acid ligands, its preparation method, and its applications. 2+ Cd-MOF materials with well-defined composition and crystal structure were constructed using aromatic tetracarboxylic acid ligands containing numerous conjugated bonds as the metal center and the ligands as the linkers. The resulting materials exhibit strong fluorescence emission properties and can selectively recognize Fe through fluorescence quenching. 3+ and Cr2O7 2- This is intended to address the limited availability of existing Cd-MOF materials with fluorescent recognition capabilities that can selectively recognize both iron and dichromate ions simultaneously, as well as the technical challenges of balancing fluorescence emission intensity, target ion selectivity, anti-interference ability, and detection sensitivity in fluorescent recognition materials.

[0011] The present invention adopts the following technical solution: A Cd-MOF material based on aromatic tetracarboxylic acid ligands, the Cd-MOF material comprising Cd 2+ With a metal center, and aromatic tetracarboxylic acid ligands 4,4′,4″,4 -([6,6′-biphenylpyrazine]-2,2′,3,3′-tetramethyl)tetrabenzoic acid tri-antion HL 3- As a coordination linker, the Cd 2+ With the HL 3- Coordination forms a metal-organic framework; the Cd-MOF material also includes Me2NH2. + Ions, N,N-dimethylacetamide molecules, and lattice water molecules.

[0012] Furthermore, the structural formula of the aromatic tetracarboxylic acid ligand is as follows:

[0013] The Cd-MOF material is a crystalline material, belonging to the orthorhombic crystal system, with space group [space group missing]. Fddd The unit cell parameters are: a = 20.66 Å, b = 24.56 Å, c = 91.62 Å, α = β = γ = 90°, V = 46497.2 Å. 3 Z=32.

[0014] Another technical solution of the present invention is a method for preparing Cd-MOF materials based on aromatic tetracarboxylic acid ligands, comprising the following steps: The aromatic tetracarboxylic acid ligand H4L and Cd(NO3)2·4H2O were added to the reaction vessel, wherein H4L was in the form of 4,4′,4″,4 -([6,6′-biphenylpyrazine]-2,2′,3,3′-tetramethyl)tetrabenzoic acid; Add a mixed solution of N,N-dimethylacetamide, H2O and HNO3 to the reaction vessel, and sonicate for 30 minutes to make the mixed solution evenly mixed with H4L and Cd(NO3)2·4H2O; The reaction vessel was sealed and heated to 120°C at a heating rate of 20°C / h, and reacted at a constant temperature for 72 hours. Then, the temperature was lowered to room temperature at a cooling rate of 2°C / h. The resulting reaction product was washed with N,N-dimethylacetamide, and after solid-liquid separation and drying, Cd-MOF material was obtained.

[0015] Furthermore, the molar ratio of the aromatic tetracarboxylic acid ligand H4L to Cd(NO3)2·4H2O is 1:4; the volume ratio of N,N-dimethylacetamide, H2O and HNO3 is 40:10:1.

[0016] Furthermore, the reaction vessel has a polytetrafluoroethylene liner; the reaction product is washed three times with N,N-dimethylacetamide, filtered, and dried to obtain yellow rod-shaped crystals.

[0017] Furthermore, the aromatic tetracarboxylic acid ligand H4L is prepared by the following method: Add 75% methanol solution to a round-bottom flask, place the round-bottom flask in an ice-water bath, add thiamine hydrochloride and stir until dissolved, then add sodium hydroxide aqueous solution, stir for 10 minutes, add methyl p-formylbenzoate, reflux at 100°C for 1 hour, and the reaction product is obtained by solid-liquid separation, washing and drying. An 80% aqueous acetic acid solution, product 1, copper acetate, and ammonium nitrate were mixed and refluxed at 105°C for 8 hours. The reaction product was then separated into solid and liquid components, washed, and dried to obtain product 2. Under a nitrogen atmosphere, 3,3-diaminobenzidine, product 2, methanol and glacial acetic acid were mixed and refluxed at 120°C for 12 hours. The reaction product was then separated into solid and liquid components, washed and dried to obtain product 3. Product 3, potassium hydroxide, and a 50% aqueous ethanol solution were mixed and refluxed at 90°C for 24 hours. After removing the ethanol, the pH was adjusted to 3 with dilute hydrochloric acid and stirred for 1 hour. After solid-liquid separation, washing to neutrality, and drying, the aromatic tetracarboxylic acid ligand H4L was obtained.

[0018] Another technical solution of the present invention is that Cd-MOF materials based on aromatic tetracarboxylic acid ligands are used for fluorescent recognition of Fe. 3+ Applications in [the field].

[0019] Furthermore, the Cd-MOF material is supplemented with Fe-containing... 3+ In a DMF solution, a suspension was formed by ultrasonic oscillation. The fluorescence emission spectrum of the suspension was measured using a fluorescence spectrophotometer. Based on Fe... 3+ The fluorescence quenching effect of the Cd-MOF material identifies Fe. 3+ .

[0020] Another technical solution of the present invention is that Cd-MOF materials based on aromatic tetracarboxylic acid ligands can recognize Cr2O7 in fluorescence. 2- Applications in [the field].

[0021] Furthermore, the Cd-MOF material is supplemented with Cr2O7. 2- In a DMF solution, a suspension was formed by ultrasonic oscillation. The fluorescence emission spectrum of the suspension was measured using a fluorescence spectrophotometer. Based on Cr2O7... 2- The fluorescence quenching effect of the Cd-MOF material identifies Cr2O7. 2- .

[0022] Compared with the prior art, the present invention has at least the following beneficial effects: A Cd-MOF material based on aromatic tetracarboxylic acid ligands, using Cd 2+ As the metal center, with 4,4′,4″,4 -([6,6′-biphenylpyrazine]-2,2′,3,3′-tetramethyl)tetrabenzoic acid tri-antion HL³ - As a coordinating linker, Cd 2+ With HL 3- Coordination forms a metal-organic framework, and the resulting Cd-MOF material also includes Me2NH2. + Ions, DMA molecules, and lattice water molecules; the aromatic tetracarboxylic acid ligand has a large conjugated system, providing a structural basis for the fluorescence emission of the material; the obtained Cd-MOF has a well-defined crystal structure and can react with Fe... 3+ and Cr2O7 2- It produces a significant fluorescence quenching response.

[0023] Furthermore, Cd-MOF belongs to the orthorhombic crystal system and has a space group of Fddd Furthermore, the cell parameters were defined to allow for more accurate characterization of the protected material through crystallographic features. Single-crystal structure testing and powder X-ray diffraction results mutually verified each other; the experimental XRD peak positions matched those obtained from single-crystal structure simulation, indicating that the obtained sample could form a Cd-MOF structure consistent with the single-crystal analysis results. This improves the certainty of material structure definition and serves as a basis for judging the consistency of the crystal phase of the prepared material.

[0024] A method for preparing Cd-MOF materials based on aromatic tetracarboxylic acid ligands is disclosed. H4L and cadmium salt are used as reactants. A mixed reaction system consisting of DMA, H2O, and HNO3 is formed. After ultrasonic dispersion, the mixture is heated to 120℃ at a rate of 20℃ / h and held at that temperature for 72h, then cooled to room temperature at a rate of 2℃ / h. Ultrasonic treatment is used to ensure thorough mixing of the reactants. The solvothermal conditions are Cd... 2+ The coordination assembly with aromatic tetracarboxylic acid ligands and the crystal growth provide a reaction environment; the limited heating, isothermal, and slow cooling processes are conducive to obtaining crystalline products with well-defined structures. Finally, yellow rod-shaped Cd-MOF crystals are obtained by washing, filtering, and drying with DMA, making the material preparation process clear and the process conditions controllable.

[0025] Furthermore, limiting the molar ratio of H4L to cadmium salt and the volume ratio of DMA, H2O, and HNO3 is used to control the composition of the coordination reactants and the mixed reaction system. These ratios correspond to the actual preparation conditions in the examples, reducing differences in crystal formation conditions caused by variations in reactant composition and solvent system. This facilitates obtaining the target Cd-MOF material according to the reaction system established in the examples and improves the reproducibility of the preparation conditions.

[0026] Furthermore, a reaction vessel with a polytetrafluoroethylene liner was used to allow the solvothermal reaction to proceed under closed conditions, reducing unnecessary interference between the reaction system and the reaction vessel. After the reaction, the crystals were washed three times with DMA to remove residual soluble components from the crystal surface and the reaction system. The resulting yellow rod-shaped crystals were obtained after filtration and drying. This method facilitates the acquisition of Cd-MOF crystal samples suitable for structural characterization and fluorescence performance testing.

[0027] Furthermore, a clear process route for the preparation of complex aromatic conjugated ligands was established by sequentially preparing the aromatic tetracarboxylic acid ligand H4L, with specific control over the reaction medium, temperature, time, and separation and washing conditions of the products at each stage. Finally, H4L was obtained through alkali treatment, acidification to pH 3, and washing to neutrality, providing a basis for subsequent reactions with Cd. 2+ Coordination assembly provides well-defined aromatic tetracarboxylic acid ligands and provides a complete implementation basis for the source materials and preparation process of Cd-MOF.

[0028] A Cd-MOF material based on aromatic tetracarboxylic acid ligands for fluorescent recognition of Fe 3+ The application of the Cd-MOF in Fe³ + Fluorescence recognition, utilizing Fe³ + The phenomenon that the addition of Fe³⁺ caused a significant decrease in the fluorescence intensity of Cd-MOF confirmed that Fe³⁺ was involved. + . with Na + K + Mg² + Al³+ Ca² + Zn² + Compared to other cations, Fe³ + It produces a significant fluorescence quenching effect; further anti-interference experiments show that it can still maintain Fe³⁺ even in the presence of other cations. + The recognition response enables this Cd-MOF to act as Fe³⁺. + Fluorescent probe materials.

[0029] Furthermore, Cd-MOF was dispersed in a DMF system, and the suspension was thoroughly mixed by sonication. Then, fluorescence emission spectra were collected using a fluorescence spectrophotometer to detect the Fe³⁺ content. + The resulting change in fluorescence intensity can be converted into a measurable spectral signal; experiments show that Fe³ + The fluorescence intensity of Cd-MOF gradually decreased with increasing concentration, ranging from 0 to 8.0 × 10⁻⁶. -5 It exhibits good linearity within the mol / L range, with a limit of detection of 1.50 × 10⁻⁶. -8 mol / L, therefore it can not only identify Fe³ + It can also be used for its quantitative detection.

[0030] A Cd-MOF material based on aromatic tetracarboxylic acid ligands in the fluorescence recognition of Cr2O7 2- In its application, the same Cd-MOF was further used in Cr2O7. 2- Fluorescence recognition. (Compared to F) - Cl - ,Br - NO3 - H2PO4 - SO4 2- CO3 2- and Ac - In comparison, Cr2O7 2- This method can significantly quench the fluorescence of Cd-MOFs and maintain the corresponding recognition response even under conditions where other anions coexist. Therefore, the same Cd-MOF can recognize not only the cation Fe³⁺ but also other anions. + It can also recognize the anion Cr2O7. 2- This expands the scope of fluorescence detection for this material.

[0031] Furthermore, by dispersing Cd-MOF in Cr2O7-containing... 2- The DMF system was analyzed and its fluorescence emission spectrum was measured. Cr2O7 was used. 2- The concentration change was correlated with the degree of fluorescence quenching in Cd-MOF. Experimental results showed that as Cr2O7 concentration decreased, the fluorescence quenching of Cd-MOF decreased. 2- With increasing concentration, the fluorescence intensity of Cd-MOF gradually decreases, ranging from 0 to 3.0 × 10⁻⁶.-4 It exhibits good linearity within the mol / L range, with a limit of detection of 4.00 × 10⁻⁶. -7 mol / L, enabling this material to be used in Cr2O7 2- Selective identification and quantitative detection.

[0032] In summary, this invention uses Cd 2+ With highly conjugated aromatic tetracarboxylic acid ligands, well-defined Cd-MOFs are constructed. The preparation conditions are controllable, and the materials exhibit strong fluorescence emission, which can be used to identify Fe³⁺ ligands through fluorescence quenching. + and Cr2O7² - It also has good selectivity, anti-interference ability and detection sensitivity.

[0033] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0034] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the following description of the relative embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0035] Figure 1 The structural diagrams of the Cd-MOF material based on aromatic tetracarboxylic acid ligands provided by the present invention are shown, wherein (a) is a coordination environment diagram and (b) is a two-dimensional structural diagram. Figure 2 Infrared spectrum of Cd-MOF material based on aromatic tetracarboxylic acid ligands provided by the present invention; Figure 3 Thermogravimetric analysis diagram of Cd-MOF material based on aromatic tetracarboxylic acid ligands provided by the present invention; Figure 4 Powder X-ray diffraction pattern of Cd-MOF material based on aromatic tetracarboxylic acid ligands provided by the present invention; Figure 5 The image shows the Cd-MOF material based on aromatic tetracarboxylic acid ligands provided by the present invention, wherein (a) is the fluorescence emission spectrum of DMF solution with different metal ions, and (b) is a comparison of the relative intensity of the emission peak at 445 nm in the spectrum; Figure 6 The diagram shows the Cd-MOF material based on aromatic tetracarboxylic acid ligands provided by this invention, wherein (a) represents the results of different concentrations of Fe. 3+ Fluorescence quenching diagram of ions, (b) shows the fluorescence of Cd-MOF material based on aromatic tetracarboxylic acid ligands quenched by Fe. 3+ The quenching of I0 / I on Fe3+ concentration c Plot the graph; the inset shows concentrations between 0 and 8.0 × 10⁻⁶. 5 I0 / I in the range of mol / L for Fe 3+ concentration c Linear fitting; Figure 7 The fluorescence quenching of Fe in Cd-MOF materials based on aromatic tetracarboxylic acid ligands provided by this invention 3+ Experimental diagram showing interference from other cations in the ion; Figure 8 The image shows the Cd-MOF material based on aromatic tetracarboxylic acid ligands provided by the present invention, wherein (a) is the fluorescence emission spectrum in DMF solutions with different anions; and (b) is a comparison of the relative intensity of the emission peak at 445 nm in the spectrum. Figure 9 The diagram shows the Cd-MOF material based on aromatic tetracarboxylic acid ligands provided by this invention, wherein (a) represents the different concentrations of Cr2O7. 2 Fluorescence quenching diagram of ions, (b) shows the fluorescence of Cd-MOF material based on aromatic tetracarboxylic acid ligands quenched by Cr2O7. 2 Quenching of I0 / I against Cr2O7 2 concentration c The illustration shows concentrations ranging from 0 to 3.0 × 10⁻⁶. 4 I0 / I in the range of mol / L for Cr2O7 2 concentration c Linear fitting; Figure 10 The fluorescence quenching of Cr2O7 based Cd-MOF material with aromatic tetracarboxylic acid ligands provided by this invention 2 Graph showing the interference of other anions on the ion. Detailed Implementation

[0036] This invention provides a Cd-MOF material based on aromatic tetracarboxylic acid ligands, its preparation method, and its applications. Addressing the problem that existing Cd-MOF fluorescent recognition materials struggle to simultaneously achieve strong fluorescence emission performance, target ion selectivity, anti-interference ability, and detection sensitivity, this invention utilizes Cd... 2+ With a metal center, and aromatic tetracarboxylic acid ligands 4,4′,4″,4 containing a large conjugated system. Using α-([6,6′-biphenylpyrazine]-2,2′,3,3′-tetramethyl)tetrabenzoic acid as a linker, Cd-MOF materials with well-defined composition and crystal structure were constructed under specific solvothermal conditions, resulting in materials with strong fluorescence emission properties; simultaneously, Fe... 3+ and Cr2O7 2 The significant fluorescence quenching response generated by this Cd-MOF enables selective recognition of two types of target ions with different properties, and maintains good anti-interference ability in the presence of other coexisting cations or anions; experimental results further show that this material is effective against Fe 3+ and Cr2O7 2 They have low detection limits and good linear response ranges, thus achieving a combination of material structure, fluorescence performance and ion detection function while maintaining simple preparation process, controllable conditions and clear chemical composition.

[0037] Example 1 This invention provides a Cd-MOF material based on aromatic tetracarboxylic acid ligands, wherein the Cd-MOF material uses Cd 2+ With a metal center, and aromatic tetracarboxylic acid ligands 4,4′,4″,4 -([6,6′-biphenylpyrazine]-2,2′,3,3′-tetramethyl)tetrabenzoic acid tri-antion HL 3- As a coordination linker, the Cd 2+ With the HL 3- Coordination forms a metal-organic framework; the Cd-MOF material also includes Me2NH2. + Ions, N,N-dimethylacetamide molecules, and lattice water molecules.

[0038] The structural formula of the aromatic tetracarboxylic acid ligand is as follows:

[0039] Cd-MOF materials are crystalline materials, belonging to the orthorhombic crystal system with space group 1. Fddd The unit cell parameters are: a =20.66Å, b =24.56Å, c =91.62Å, α = β = γ =90º V =46497.2Å 3 , Z =32.

[0040] This invention provides a method for preparing Cd-MOF materials based on aromatic tetracarboxylic acid ligands, specifically comprising the following steps: S1. Add 0.036g H4L and 0.062g Cd(NO3)2·4H2O to the polytetrafluoroethylene liner of the reactor; The preparation process of the aromatic tetracarboxylic acid ligand H4L provided by the present invention includes the following specific steps: S101. A 75% methanol solution (7.5 mL of methanol and 2.5 mL of deionized water) was added to a round-bottom flask. The flask was then placed in an ice-water bath. 1.69 g of thiamine hydrochloride was added, and the mixture was stirred until the solid dissolved. 0.25 mL of freshly prepared sodium hydroxide aqueous solution was slowly added dropwise, and the mixture was stirred at high speed for 10 min. 14.76 g of methyl p-formylbenzoate was then added. The mixture was heated to 100 °C and refluxed for 1 hour. After the reaction was complete, the mixture was allowed to cool to room temperature, filtered, and the solid was washed successively with deionized water, methanol, and diethyl ether. After drying, a white solid was obtained, designated as product 1, with a yield of 83%. S102. 35 mL of 80% acetic acid aqueous solution, 19.20 g of product 1, 0.10 g of copper acetate, and 5.04 g of ammonium nitrate were sequentially added to a round-bottom flask. The mixture was heated to 105 °C and refluxed for 8 hours. After the reaction was complete, the mixture was cooled to room temperature, filtered, and the solid product was washed sequentially with deionized water, methanol, and diethyl ether. After drying, a yellow-green solid powder was obtained, designated as product 2, with a yield of 91%. S103. Under a nitrogen atmosphere, 1.98 g of 3,3-diaminobenzidine, 6.53 g of product 2, 37.5 mL of methanol, and 112.5 mL of glacial acetic acid were sequentially added to a round-bottom flask. The mixture was heated to 120 °C and refluxed for 12 hours. After the reaction was complete, the mixture was cooled to room temperature, filtered, and the solid product was washed sequentially with methanol and tetrahydrofuran. After drying, a yellowish-brown solid powder was obtained, designated as product 3, with a yield of 79%. S104. 3.89 g of product 3, 1.4 g of potassium hydroxide, and 120 mL of 50% ethanol aqueous solution were added to a round-bottom flask. The mixture was refluxed at 90 °C for 24 hours. After the reaction was complete, the mixture was cooled to room temperature, and the ethanol in the solvent was removed by rotary evaporation. The pH was adjusted to 3 with dilute hydrochloric acid, and stirring was continued for 1 hour. The product was filtered, washed with deionized water until neutral, and dried to obtain a yellow solid powder, which was aromatic tetracarboxylic acid H4L, with a yield of 89%.

[0041] S2. Continue to add a mixed solution of 8 mL DMA, 2 mL H2O and 0.2 mL HNO3 to the liner of the reactor, and sonicate for 30 minutes to make the mixed solution and the substances in step S1 mix evenly. S3. Seal the reactor and place it in an oven. Increase the temperature to 120°C at a rate of 20°C / h and maintain the temperature for 72 hours. Then, decrease the temperature from 120°C to room temperature at a rate of 2°C / h. Wash the reaction product three times with DMA solvent, filter, and dry to obtain yellow rod-shaped crystals, which are the Cd-MOF material.

[0042] To illustrate the characteristics of the cadmium metal-organic framework material Cd-MOF and the aromatic tetracarboxylic acid ligand H4L prepared in Example 1, the following experiments 1-4 were conducted, and the corresponding... Figures 1-4 Please provide a detailed explanation.

[0043] Experiment 1: Structural characterization of cadmium metal-organic framework (Cd-MOF) materials: To determine the crystal structure of Cd-MOF, the Cd-MOF crystal obtained in Example 1 was tested on a Rigaku Oxford Diffraction diffractometer at a temperature of 100 K. The test used Cu-K crystals monochromated with a graphite monochromator. a Rays serve as the light source; where Cu-K a The wavelength of the ray is λ = 0.71073 Å; ω-φ Diffraction points were collected using a scanning method; non-hydrogen atoms were solved using a direct method, and their coordinates and anisotropy parameters were determined using a method based on... F 2 The matrix was refined using the least squares method, and the positions of hydrogen atoms were obtained through theoretical hydrogen addition and Fourier peak finding. All calculations were performed using the SHELXS-2013 and SHELXL-2013 software packages; the obtained crystallographic data are shown in Table 1 (Cd-MOF crystallographic parameters); the coordination environment diagram and three-dimensional structure diagram of the Cd-MOF crystal structure are shown in [reference needed]. Figure 1 As shown.

[0044] Table 1 Crystallographic parameters of Cd-MOF

[0045] Figure 1 The coordination environment diagram and three-dimensional framework structure diagram of the Cd-MOF material in Example 1 are given. From... Figure 1 (a) It can be seen that the smallest asymmetric unit cell of the Cd-MOF material contains one crystallographically independent Cd. 2+ Ions, 1 HL 3 Ligand, 1 Me2NH2 + The mixture contains ions, four free DMA molecules, and one lattice water molecule. The central Cd group... 2+ Ions from three HL 3 The six carboxyl oxygen atoms of the ligand coordinate to form a six-coordinate octahedral geometry; each HL 3 The three carboxyl groups in the ligand participate in the interaction of three Cd groups. 2+ The ion coordinates, with one remaining carboxyl group not participating in the coordination. (Cd) 2+ Ions communicate with each other via HL 3 Ligand linkages ultimately form a three-dimensional framework structure, such as Figure 1 As shown in (b).

[0046] Experiment 2: Infrared characterization of Cd-MOF materials: The Cd-MOF material from Example 1 and the aromatic tetracarboxylic acid ligand H4L were tested at 4000~400 cm⁻¹ using a Bruker VERTEX 70 instrument. -1 Infrared spectra within the range, results can be found in [reference needed]. Figure 2 ;from Figure 2 As can be seen from this, the IR (cm²) of Cd-MOF materials... 1 : 3388 (s), 2788 (m), 1588 (s), 1545 (s), 1473 (m), 1385 (s), 1341 (s), 1181 (m), 1138 (m), 1102 (w), 1055 (m), 1014 (m), 809 (m), 719 (m), 551 (w). IR (cm²) of ligand H4L 1 ): 3415(m), 1682(m), 1605(s), 1556(w), 1507(w), 1473(w), 1385(m), 1208(w), 1014(w), 776(m), 707(m).

[0047] Experiment 3: Thermogravimetric characterization of Cd-MOF materials: The thermogravimetric analysis (TGA / SDTA851) was used to test the thermogravimetric properties of the Cd-MOF material prepared in Example 1, and the results were as follows: Figure 3 The thermogravimetric analysis diagram is shown below. Figure 3 As can be seen, Cd-MOF experiences slight weight loss from room temperature to around 50°C. With further increases in temperature, Cd-MOF rapidly loses weight, reaching approximately 16.49% at around 165°C, corresponding to the loss of 3 DMA molecules and 1 H2O molecule, slightly lower than the theoretical weight loss of 17.25%. With further increases in temperature, within the range of 165–335°C, the weight loss is approximately 9.73%, corresponding to the loss of 1 DMA molecule and the dimethylamine cation (Me2NH2). +The value is close to the corresponding theoretical weight loss of 10.15%. When the temperature is higher than 335℃, the thermogravimetric curve drops rapidly, indicating that the organic matter in Cd-MOF decomposes and the skeleton collapses after the temperature is higher than 335℃.

[0048] Experiment 4 Powder X-ray diffraction characterization of Cd-MOF materials: For the Cd-MOF material in Example 1, the XRD curves of the ground powder crystals were measured using an X-ray diffractometer. The results were compared with the XRD curves of the single-crystal structure data of Cd-MOF fitted using MERCURY software. Figure 4 ;from Figure 4 The results show that the peak positions of the experimentally tested XRD of the Cd-MOF material are consistent with those of the simulated XRD, indicating that the sample structure is consistent with the structure of the Cd-MOF material tested in single crystal.

[0049] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0050] Example 2 A fluorescence-selective recognition experiment of Cd-MOF materials based on aromatic tetracarboxylic acid ligands: Fluorescence spectroscopy was performed at room temperature using a Lumina fluorescence spectrophotometer. The test conditions were set as follows: excitation wavelength of 295 nm, excitation and emission slit widths of 10 nm and 20 nm, respectively, and photomultiplier tube voltage of 400 V.

[0051] Under dark-box ultraviolet light irradiation, Cd-MOF exhibits bright blue-green fluorescence, indicating that the MOF has good fluorescence emission performance. In this invention, Cd-MOF was prepared into a 1 mg / mL DMF suspension, and relevant fluorescence performance tests were conducted.

[0052] Fluorescence selective recognition blank group experiment: To ensure the reliability of experimental data, before each sample measurement, 2 mC d-MOF suspension was transferred into a fluorescent cuvette without adding any guest molecules. The fluorescence spectrum of the blank sample was measured three times consecutively at an excitation wavelength of 295 nm, and the average value was taken or the fluorescence signal was confirmed to be stable.

[0053] To test the fluorescence recognition of Cd-MOF materials in DMF solution under different cation presence conditions, the following experiments were conducted: (1) Accurately weigh 84 mg of Cd-MOF from Example 1, add 84 mL of DMF, sonicate for 20 minutes, and prepare a DMF suspension of Cd-MOF with a concentration of 1 mg / mL.

[0054] (2) Calculate and weigh a certain mass of nitrates of different metal ions (NaNO3, KNO3, Mg(NO3)2, Al(NO3)3, Ca(NO3)2, Zn(NO3)2, Cd(NO3)2, Ni(NO3)2, Pb(NO3)2, Hg(NO3)2, Co(NO3)2, AgNO3, Cr(NO3)3 and Fe(NO3)3), and prepare a solution of 0.01×10 5 A metal ion solution with a concentration of mol / L.

[0055] (3) Transfer 2 mL of the Cd-MOF suspension from step (1) into a cuvette, add 20 μL of the nitrate solution from step (2), and mix thoroughly by ultrasonic oscillation. Measure the fluorescence emission spectrum of the system using a fluorescence spectrophotometer. Set the excitation wavelength to 295 nm, the excitation and emission slit widths to 10 nm and 20 nm respectively, and the photomultiplier tube voltage to 400 V. Test the fluorescence spectra of each mixed solution in the range of 300–700 nm, such as… Figure 5 a; Record the fluorescence intensity at 445 nm for each fluorescence spectrum; Plot each metal ion in the detection system on the x-axis and the fluorescence intensity at 445 nm on the y-axis to obtain the following results: Figure 5 The experimental results are shown in b.

[0056] Please see Figure 5 Na at the same concentration + K + Mg 2+ Al 3+ Ca 2+ Zn 2+ Cd 2+ Ni 2+ Pb 2+ Hg 2+ Co 2+ Ag +Cr 3+ and Fe 3+ Compared to the fluorescence intensity of plasma, Fe-containing plasma... 3+ The fluorescence intensity of the Cd-MOF DMF suspension was the weakest, indicating that the Cd-MOF DMF suspension has the weakest fluorescence intensity for Fe. 3+ The ions exhibit significant selective recognition, and the phenomenon of reduced fluorescence intensity is called fluorescence quenching.

[0057] This invention aims to test the effect of Cd-MOF on different concentrations of Fe. 3+ Ion fluorescence quenching. The following fluorescence titration experiments were performed on each cation: Take 17 5 mL reaction flasks and add 2 mL of the DMF suspension of Cd-MOF prepared in the selective recognition experiment to each flask. Then, add 2 μL of 0.01 mol·L⁻¹ solution to each flask successively. 1 The Fe(NO3)3 DMF solution was thoroughly mixed after each addition and tested on a fluorescence spectrophotometer. The excitation wavelength was set to 295 nm, and the excitation and emission slits were 10 nm and 20 nm, respectively. The fluorescence spectra of the above mixed solutions in the 300–700 nm range were measured, and the results are as follows: Figure 6 As shown in (a).

[0058] Please see Figure 6 (a) With Fe 3+ With increasing Fe concentration, the fluorescence intensity of the DMF suspension of Cd-MOF material gradually decreased, indicating that Fe 3+ Cd-MOF materials exhibit fluorescence quenching effects. Cd-MOF materials exhibit fluorescence quenching effects on Fe... 3+ The lowest fluorescence detection limit for the ion is 1.50 × 10⁻⁶. 8 mol / L. The fluorescence intensity (I0 / I, where I0 and I are respectively the concentrations of Fe2+ added.) 3+ (Fluorescence intensity of Cd-MOF before and after ionization) for Fe 3+ Plotting ion concentrations, such as... Figure 6 As shown in (b), the results range from 0 to 8.0 × 10⁻⁶. 5 The mol / L ratio showed a good linear relationship. Therefore, in the range of 0~8.0×10⁻⁶, the linear relationship was observed. 5 Quantitatively targeting Fe within the mol / L concentration range is possible. 3+ Perform the test. According to Stern Volmer (I0 / I) 1 = K SV Equation C, (K) SV(where I0 and I0 are the quenching constants, I0 and I0 are the fluorescence intensities of Cd-MOF before and after the addition of quenching ions, respectively, and C is the concentration of quenching ions). The Cd-MOF material is used to quench Fe... 3+ Ions in the range of 0~8.0×10 5 Linear fitting was performed on the fluorescence quenching effect in the mol / L range, such as... Figure 6 (b) K is obtained by fitting. SV =1.72×10 5 mol / L indicates that the Cd-MOF material is effective against Fe 3+ Ions exhibit high fluorescence response sensitivity.

[0059] This invention aims to test the interference resistance of Cd-MOF to other cations. Cation interference resistance experiments were conducted on various cations, and the specific operational steps are as follows: Transfer 2 mL of Cd-MOF DMF suspension into a cuvette, then add 2 μL of a 1 mol·L⁻¹ solution. 1 Interfering ion solution M(NO3) n (M) n+ =Na + K + Mg 2+ Al 3+ Ca 2+ Zn 2+ Cd 2+ Ni 2+ Pb 2+ Hg 2+ Co 2+ Ag + and Cr 3+ After shaking and mixing, the fluorescence intensity at a wavelength of 445 nm was measured; then 2 μL of a 1 mol·L⁻¹ solution was added. 1 Fe 3+ The ionic solution was shaken again to mix thoroughly, thus ensuring the presence of Fe. 3+ Other cations also exist alongside the ions. Fluorescence spectra were measured at wavelengths of 300–700 nm using a fluorescence spectrophotometer. The results are as follows: Figure 7 As shown.

[0060] from Figure 7 As can be seen, the Cd-MOF detection system still maintains the corresponding fluorescence response after the addition of the interfering cations; further addition of Fe 3+ Subsequently, the fluorescence of Cd-MOF in each mixed detection system was significantly quenched, indicating that the presence of the other cations did not affect the fluorescence of Fe. 3+The fluorescence recognition of the Cd-MOF material is significantly interfered with, indicating that the Cd-MOF material is susceptible to interference from Fe. 3+ It has good fluorescence recognition selectivity and anti-interference ability.

[0061] Example 3 This embodiment aims to test the fluorescence recognition of Cd-MOF materials in DMF solution under different anion conditions.

[0062] This embodiment selects the Cd-MOF material provided in Example 1, and the specific process is as follows: (1) Accurately weigh 72 mg of Cd-MOF from Example 1, add 72 mL of DMF, sonicate for 20 minutes, and prepare a DMF suspension of Cd-MOF with a concentration of 1 mg / mL.

[0063] (2) Calculate and weigh a certain mass of the following sodium or potassium salts: NaF, NaCl, NaBr, NaNO3, NaH2PO4, Na2SO4, Na2CO3, NaAc and K2Cr2O7, and prepare a solution of 1×10 4 Anion solutions with a concentration of mol / L.

[0064] (3) Transfer 2 mL of the Cd-MOF suspension from step (1) into a cuvette, add 20 μL of the sodium or potassium salt solution from step (2), mix thoroughly by ultrasonic oscillation, and then measure the fluorescence emission spectrum of the system using a fluorescence spectrophotometer; test the fluorescence spectrum of each mixed solution in the range of 300~700 nm, such as... Figure 8 As shown in (a); record the fluorescence intensity of each fluorescence spectrum at 445 nm, and plot each anion in the detection system as the abscissa and the fluorescence intensity at 445 nm as the ordinate, to obtain the following results. Figure 8 The experimental results are shown in (b).

[0065] from Figure 8 It can be seen that F at the same concentration Cl ,Br NO3 H2PO4 SO4 2 CO3 2 Ac and Cr2O7 2 Compared to the fluorescence intensity of plasma, that containing Cr2O7 2 The fluorescence intensity of the Cd-MOF DMF suspension was the weakest, indicating that the Cd-MOF DMF suspension can selectively recognize Cr2O7 through fluorescence quenching. 2 ion.

[0066] This invention aims to test the effect of Cd-MOF on different concentrations of Cr2O7. 2 Ion fluorescence quenching. The following fluorescence titration experiments were performed on each anion: 26 reaction flasks (5 mL each) were filled with 2 mL of DMF suspension of Cd-MOF prepared in the selective recognition experiment, followed by the addition of 2 μL of 0.01 mol·L⁻¹ solution. 1 The K₂Cr₂O₇ DMF solution was thoroughly mixed after each addition, and the samples were tested on a fluorescence spectrophotometer. The excitation wavelength was set to 295 nm, and the excitation and emission slits were set to 10 nm and 20 nm, respectively. The fluorescence spectra of the above mixed solutions in the 300–700 nm range were measured, and the results are as follows: Figure 9 As shown in (a).

[0067] Please see Figure 9 (a) With Cr2O7 2 As the concentration increased, the fluorescence intensity of the DMF suspension of Cd-MOF material gradually decreased, indicating that Cr2O7 2 Cd-MOF materials exhibit fluorescence quenching effects. Cd-MOF materials exhibit fluorescence quenching effects on Cr2O7. 2 The lowest fluorescence detection limit for the ion is 4.00 × 10⁻⁶. 7 mol / L. The fluorescence intensity (I0 / I, where I0 and I are respectively the values ​​of Cr2O7 added. 2 (Fluorescence intensity of Cd-MOF before and after ionization) for Cr2O7 2 Plotting ion concentrations, such as... Figure 9 As shown in (b), the results range from 0 to 3.0 × 10⁻⁶. 4 The mol / L ratio showed a good linear relationship. Therefore, in the range of 0~3.0×10⁻⁶, the linear relationship was observed. 4 Cr2O7 can be quantitatively controlled within the mol / L concentration range. 2 Perform the test. According to Stern Volmer (I0 / I) 1 = K SV Equation C, (K)SV (where I0 and I0 are the quenching constants, I0 and I0 are the fluorescence intensities of Cd-MOF before and after the addition of quenching ions, respectively, and C is the concentration of quenching ions). The Cd-MOF material is compared with Cr2O7. 2 Ions in the range of 0~3.0×10 4 Linear fitting was performed on the fluorescence quenching effect in the mol / L range ( Figure 9 b-insertion plot), fitted to obtain K SV =4.46×10 3 mol / L indicates that Cd-MOF materials are effective against Cr2O7. 2 It has high fluorescence response sensitivity.

[0068] This invention aims to test the anti-interference performance of Cd-MOF against other anions. Anti-interference experiments were conducted on various anions, and the specific operating steps are as follows: Transfer 2 mL of Cd-MOF DMF suspension into a cuvette, then add 2 μL of a 1 mol·L⁻¹ solution. 1 Interfering ion solution Na n X (X) n =F Cl ,Br NO3 H2PO4 SO4 2 CO3 2 and Ac After shaking and mixing, the fluorescence intensity at a wavelength of 445 nm was measured; then 2 μL of a 1 mol·L⁻¹ solution was added. 1 Cr2O7 2 The ionic solution was shaken again to mix thoroughly, thus ensuring the presence of Cr₂O₇. 2 Other anions are present along with the ions. Fluorescence spectra at wavelengths of 300–700 nm were measured using a fluorescence spectrophotometer. The results are as follows: Figure 10 As shown.

[0069] from Figure 10 As can be seen, the Cd-MOF detection system still maintains the corresponding fluorescence response after the addition of the interfering anions; further addition of Cr2O7 2 Subsequently, the fluorescence of Cd-MOF in each mixed detection system was significantly quenched, indicating that the presence of the other anions did not affect the fluorescence of Cr2O7. 2 The fluorescence recognition of the Cd-MOF material is significantly interfered with, indicating that the Cd-MOF material does not effectively detect Cr2O7. 2 It has good fluorescence recognition selectivity and anti-interference ability.

[0070] The preparation process of the Cd-MOF material based on aromatic tetracarboxylic acid ligands of the present invention is simple, with controllable process conditions and easily controllable chemical composition. It can be used as a fluorescent recognition and detection material for iron ions (Fe... 3+ ) and dichromate (Cr2O7) 2 It exhibits excellent selectivity, anti-interference ability and high sensitivity in the detection of ).

[0071] In summary, this invention provides a Cd-MOF material based on aromatic tetracarboxylic acid ligands, its preparation method, and its applications, using Cd... 2+ With a metal center and aromatic tetracarboxylic acid ligands containing numerous conjugated bonds as linkers, Cd-MOFs with well-defined composition and crystal structure were constructed via a solvothermal reaction in a mixed system of DMA, H₂O, and HNO₃. The resulting material belongs to an orthorhombic crystal system. Fddd The space group possesses abundant porous structure and strong fluorescence emission properties. Utilizing Fe... 3+ and Cr2O7 2- The resulting fluorescence quenching effect enables the recognition of two types of target ions separately, and maintains good selectivity and anti-interference ability under conditions where other cations or anions coexist. Experiments show that it is effective for Fe... 3+ and Cr2O7 2- The detection limits were 1.50 × 10⁻⁶. -8 mol / L and 4.00×10 -7 The concentration is mol / L and exhibits a good linear relationship. This scheme balances controllable material structure, well-defined preparation conditions, and high detection sensitivity, making it suitable for Fe... 3+ and Cr2O7 2- Fluorescence detection provides a novel Cd-MOF probe material.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A Cd-MOF material based on aromatic tetracarboxylic acid ligands, characterized in that, The Cd-MOF material comprises Cd 2+ With a metal center, and aromatic tetracarboxylic acid ligands 4,4′,4″,4 -([6,6′-biphenylpyrazine]-2,2′,3,3′-tetramethyl)tetrabenzoic acid tri-antion HL 3- As a coordination linker, the Cd 2+ With the HL 3- Coordination forms a metal-organic framework; the Cd-MOF material also includes Me2NH2. + Ions, N,N-dimethylacetamide molecules, and lattice water molecules.

2. The Cd-MOF material based on aromatic tetracarboxylic acid ligands according to claim 1, characterized in that, The structural formula of the aromatic tetracarboxylic acid ligand is as follows: The Cd-MOF material is a crystalline material, belonging to the orthorhombic crystal system, with space group [space group missing]. Fddd The unit cell parameters are: a = 20.66 Å, b = 24.56 Å, c = 91.62 Å, α = β = γ = 90°, V = 46497.2 Å. 3 Z=32.

3. A method for preparing Cd-MOF materials based on aromatic tetracarboxylic acid ligands, characterized in that, Includes the following steps: The aromatic tetracarboxylic acid ligand H4L and Cd(NO3)2·4H2O were added to the reaction vessel, wherein H4L was in the form of 4,4′,4″,4 -([6,6′-biphenylpyrazine]-2,2′,3,3′-tetramethyl)tetrabenzoic acid; Add a mixed solution of N,N-dimethylacetamide, H2O and HNO3 to the reaction vessel, and sonicate for 30 minutes to make the mixed solution evenly mixed with H4L and Cd(NO3)2·4H2O; The reaction vessel was sealed and heated to 120°C at a heating rate of 20°C / h, and reacted at a constant temperature for 72 hours. Then, the temperature was lowered to room temperature at a cooling rate of 2°C / h. The resulting reaction product was washed with N,N-dimethylacetamide, and after solid-liquid separation and drying, Cd-MOF material was obtained.

4. The method for preparing Cd-MOF materials based on aromatic tetracarboxylic acid ligands according to claim 3, characterized in that, The molar ratio of the aromatic tetracarboxylic acid ligand H4L to Cd(NO3)2·4H2O is 1:4; the volume ratio of N,N-dimethylacetamide, H2O and HNO3 is 40:10:

1.

5. The method for preparing Cd-MOF materials based on aromatic tetracarboxylic acid ligands according to claim 3 or 4, characterized in that, The reaction vessel has a polytetrafluoroethylene liner; the reaction product is washed three times with N,N-dimethylacetamide, filtered, and dried to obtain yellow rod-shaped crystals.

6. The method for preparing Cd-MOF materials based on aromatic tetracarboxylic acid ligands according to claim 3, characterized in that, The aromatic tetracarboxylic acid ligand H4L was prepared by the following method: Add 75% methanol solution to a round-bottom flask, place the round-bottom flask in an ice-water bath, add thiamine hydrochloride and stir until dissolved, then add sodium hydroxide aqueous solution, stir for 10 minutes, add methyl p-formylbenzoate, reflux at 100°C for 1 hour, and the reaction product is obtained by solid-liquid separation, washing and drying. An 80% aqueous acetic acid solution, product 1, copper acetate, and ammonium nitrate were mixed and refluxed at 105°C for 8 hours. The reaction product was then separated into solid and liquid components, washed, and dried to obtain product 2. Under a nitrogen atmosphere, 3,3-diaminobenzidine, product 2, methanol and glacial acetic acid were mixed and refluxed at 120°C for 12 hours. The reaction product was then separated into solid and liquid components, washed and dried to obtain product 3. Product 3, potassium hydroxide, and a 50% aqueous ethanol solution were mixed and refluxed at 90°C for 24 hours. After removing the ethanol, the pH was adjusted to 3 with dilute hydrochloric acid and stirred for 1 hour. After solid-liquid separation, washing to neutrality, and drying, the aromatic tetracarboxylic acid ligand H4L was obtained.

7. The Cd-MOF material based on aromatic tetracarboxylic acid ligands as described in claim 1 or 2 in the fluorescence recognition of Fe 3+ Applications in [the field].

8. The application according to claim 7, characterized in that, The Cd-MOF material was added to a Fe-containing... 3+ In a DMF solution, a suspension was formed by ultrasonic oscillation. The fluorescence emission spectrum of the suspension was measured using a fluorescence spectrophotometer. Based on Fe... 3+ The fluorescence quenching effect of the Cd-MOF material identifies Fe. 3+ .

9. The Cd-MOF material based on aromatic tetracarboxylic acid ligands as described in claim 1 or 2 in the fluorescence recognition of Cr2O7 2- Applications in [the field].

10. The application according to claim 9, characterized in that, The Cd-MOF material was added with Cr2O7. 2- In a DMF solution, a suspension was formed by ultrasonic oscillation. The fluorescence emission spectrum of the suspension was measured using a fluorescence spectrophotometer. Based on Cr2O7... 2- The fluorescence quenching effect of the Cd-MOF material identifies Cr2O7. 2- .